Review of Nazianzuslu Grigorius ve Kutsal Ruh’un Tanrılığı Meselesi, by Elif Tokay - Philip Dorrol (Oksident, 2023)
Dr. Elif Tokay’s recent book- Gregory of Nazianzus and the Issue of the Divinity of the Holy Spirit- is an important milestone in the study of Christian theology. This book is the first study of Gregory of Nazianzus ever to be written and published in Turkish. It is an insightful, accessible, and thorough examination of Gregory’s profound theological vision, the central argument of which is that the triune nature of God is revealed through God’s plan of salvation for humanity. Because his Trinitarian theology was fundamental to the development of Christian doctrine in general, Gregory’s importance in the history of Christianity cannot be overstated. In addition, his spiritual vision is of particular importance in Eastern Orthodox Christianity. Gregory’s spiritual vision argues that humanity is created for the purpose of union with its Creator, and that the ascetic, contemplative, liturgical, and moral labor of the human individual all work in free cooperation with God’s saving plan. This theological anthropology is foundational to Eastern Orthodox spiritual teaching. Gregory’s works have for centuries been among the most widely read in the entire Eastern Orthodox tradition, and his theology of theosis (which Tokay discusses in detail) has played a key role in Eastern Orthodox religious practice and identity. Tokay’s analysis demonstrates that Gregory’s theology is best understood as a synthesis of doctrine and spirituality, where God’s saving role in history is the key to understanding God’s triune nature as disclosed to humanity in revelation.